Optimizing mechanical properties of AA7075 Metal Matrix Composites reinforced with TiB2 and ZrO2 particulates - Nagaraj S. Dhongade; Vinod Kumar V. Meti; I. G. Siddhalingeshwar; G. U. Raju; M. A. Umarfarooq; N.R. Banapurmath; Ashok M. Sajjan; Vinayak S. Uppin; Balbir Singh (Fracture and Structural Integrity, 2025)
Hybrid metal matrix composites (MMCs), recognized for their superior strength-to-weight ratios and synergistic property enhancements, are emerging as advanced materials capable of mitigating the inherent limitations observed in conventional monolithic composites. While traditional composites offer structural benefits, their susceptibility to creep deformation and abrasive wear restricts their broader applicability. In sectors such as aerospace, automotive, and marine engineering, aluminum-based hybrid MMCs reinforced with ceramic particulates like titanium diboride (TiB2) and zirconium dioxide (ZrO₂) have garnered considerable interest due to their enhanced mechanical integrity and tribological performance. This investigation is an extension of previous work by authors AA7075 MMCs. This work systematically examines the influence of TiB2 (fixed at 5 wt%) coupled with incremental ZrO₂ reinforcement levels (2, 4, and 6 wt%) on the microstructure, mechanical strength, hardness, and wear resistance of AA7075 alloys fabricated via the stir casting process. The study aims to elucidate the compositional optimization of hybrid reinforcements to tailor material properties for high-performance applications. Microstructural analysis revealed an equiaxed grain structure with uniform reinforcement distribution, particularly in AA7075/5% TiB2/4% ZrO2 composition. The addition of reinforcements improved hardness up to 85.45%, increasing from 55 Hv (base alloy) to 102.40 Hv. And, also the yield strength increased from 107 MPa (base alloy) to 123 MPa, an increase of 15%, attributed to the improved particle detachment resistance. Introducing TiB2 and ZrO2 particles remarkably enhanced wear resistance with a wear rate of 155 µm with 10N load due to reinforcements that act as the lubricating agent between the metal matrix and the rotating disc. Among the compositions studied, AA7075/5% TiB2/4% ZrO2 exhibited superior performance, highlighting the potential of tailored hybrid composites for advanced mechanical and tribological applications in automotive, aerospace and marine industries.